Agricultural Biotechnology: Country case studies - a Decade of Development - Persley, Gabrielle J (CABI, 2014)
Biotechnology is having a profound impact on Agricultural research and productivity, and developing countries need to organize their national research systems accordingly. Expertise in the basic biological sciences is still in short supply in many developing countries, though great strides have been made in training during the past decade. Mobilization of the basic science laboratories usually found in the universities to solve agricultural problems will require new policy and institutional arrangements and additional resources.